1999
DOI: 10.1017/s0140525x99002046
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of the structure of personality: Dopamine, facilitation of incentive motivation, and extraversion

Abstract: Extraversion has two central characteristics: (1) interpersonal engagement, which consists of affiliation (enjoying and valuing close interpersonal bonds, being warm and affectionate) and agency (being socially dominant, enjoying leadership roles, being assertive, being exhibitionistic, and having a sense of potency in accomplishing goals) and (2) impulsivity, which emerges from the interaction of extraversion and a second, independent trait (constraint). Agency is a more general motivational dispositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

94
1,600
5
22

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,755 publications
(1,721 citation statements)
references
References 135 publications
94
1,600
5
22
Order By: Relevance
“…Animal models of brain reward function are relevant to understanding positive mood effects in humans to the extent that positive emotions can be viewed as subjective cues that motivate approach behavior toward rewards (Depue and Collins 1999). Findings from animal studies indicate that fluoxetine heightens responsivity to rewards, and suggest dopaminergic (DA) and serotonergic (5-HT) mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models of brain reward function are relevant to understanding positive mood effects in humans to the extent that positive emotions can be viewed as subjective cues that motivate approach behavior toward rewards (Depue and Collins 1999). Findings from animal studies indicate that fluoxetine heightens responsivity to rewards, and suggest dopaminergic (DA) and serotonergic (5-HT) mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…reverses diminished responding to rewarding stimuli; Harrison et al 2001). To the extent that diminished positive affect is associated with diminished reinforcing value of approach behavior to rewards (Depue and Collins 1999), fluoxetine might buffer the losses in positive affect associated with quitting smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that approach and avoidance systems have partially distinct neural substrates is also quite prominent today, in varying forms (e.g., Cloninger, 1987;Davidson, 1998;Depue & Collins, 1999;Fowles, 1980;Gray, 1994aGray, , 1994bPizzagalli, Sherwood, Henriques, & Davidson, 2005).…”
Section: Background: Approach and Avoidance Asmentioning
confidence: 99%
“…Specifically, impulsivity was distinct from sensationseeking, thus failing to support any suggestion that impulsivity was intrinsically related to this concept (e.g. Acton, 2003;Depue & Collins, 1999;Kelly et al, 2006;Moeller et al 2002;Sher & Trull, 1994;Zuckerman et al, 1993) and/or was an adult-form of sensation-seeking (Clayton, Segress & Caudill, 2007). Thus, in samples where there are known to be increased levels of sensation-seeking and impulsivity (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…It is closely related to other personality constructs associated with substance use, such as impulsivity (e.g. Acton, 2003;;Ersche, et al, 2010;Moeller et al 2002), openness to experience and extraversion (Grekin, Sher & Wood, 2006), with considerable cross-over across these constructs (Depue & Collins, 1999;Kelly et al, 2006;Sher & Trull, 1994;Zuckerman et al, 1993). For example, some researchers have suggested that extraversion is an indirect test of sensation-seeking (Sher & Trull, 1994), with impulsivity a reconceptualised 'adult' form of sensation-seeking (Clayton, Segress & Caudill, 2007).…”
mentioning
confidence: 99%